2021
DOI: 10.1002/jcp.30553
|View full text |Cite
|
Sign up to set email alerts
|

The role of exosomes from BALF in lung disease

Abstract: Exosomes are released from a variety of immune cells and nonimmune cells, the phospholipid vesicle bilayer membrane structure actively secreted into tissues. Recently, exosomes were demonstrated to be effectively delivered proteins, cholesterol, lipids, and amounts of DNA, mRNA, and noncoding RNAs to a target cell or tissue from a host cell. These can be detected in blood, urine, exhaled breath condensates, bronchoalveolar lavage fluid (BALF), ascites, and cerebrospinal fluid. BALF is a clinical examination me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 86 publications
1
26
0
Order By: Relevance
“…Once entering the extracellular space, exosomes are absorbed by adjacent cells or enter the blood circulation to reach distant targets and release genetic materials, protein, and lipid mediators. In recent years, it has been observed that exosomes can transmit information between cells and regulate the function of receptor cells through paracrine and other pathways [ 19 , 32 ]. Physiologically, exosomes have been proved to be the key mediators in maintaining the steady-state function of complex thin-walled lung tissue and airway structure [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Once entering the extracellular space, exosomes are absorbed by adjacent cells or enter the blood circulation to reach distant targets and release genetic materials, protein, and lipid mediators. In recent years, it has been observed that exosomes can transmit information between cells and regulate the function of receptor cells through paracrine and other pathways [ 19 , 32 ]. Physiologically, exosomes have been proved to be the key mediators in maintaining the steady-state function of complex thin-walled lung tissue and airway structure [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, exosomes have been proved to be the key mediators in maintaining the steady-state function of complex thin-walled lung tissue and airway structure [ 33 ]. In addition to being a biomarker for diagnosis and prognosis, exosomes have also been reported to play a role in the chronic inflammatory response of the airway and lung tissue and induce the migration of inflammatory cells [ 19 ], indicating their effect on COPD genesis and progression [ 22 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes are present in all biological fluids including cerebrospinal fluid, blood, saliva, urine, amniotic fluid, ascites, and bronchoalveolar lavage fluid [6,8,9]. Exosomes transport various cargoes including proteins, lipids, various RNA species, and DNA [4].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, preventive, diagnostic, and therapeutic strategies that target or use exosomes are likely to be effective and have significant potential in a clinical setting. Exosomes contain multivesicular body-related proteins, such as apoptosis-linked gene 2-interacting protein X (Alix); tumour susceptibility gene 101 (TSG101); the endosomal sorting complex required for transport complex (in late endosomes); heat shock proteins, such as HSP70 and HSP90; proteins involved in intracellular transport, such as Rab GTPase; and transmembrane protein family tetraspanins, such as CD9, CD61, and CD81, in addition to endosome membrane-derived lipids, such as cholesterol and sphingomyelin, whose expression levels differ based on the cell type from which they are secreted [ 195 , 196 , 197 , 198 , 199 ]. Exosomes are classified based on size; ~35 nm particles are referred to as exomeres, 60–80 nm particles as small exosomes, and 90–120 nm particles as large exosomes [ 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 ], all of which exhibit different expression patterns for proteins, lipids, nucleic acids, and N-glycans.…”
Section: Introductionmentioning
confidence: 99%